Diseño y fabricación de un dispositivo electromecánico para el lavado de loza en el hogar (2022)
However, worldwide different companies and people have chosen to create devices that help us in the task of washing earthenware; first of all we find robust devices that occupy large areas or small devices that decrease their washing capacity by 70%; secondly, devices that take around 2 hours to wash a batch of earthenware knowing that it can be done manually in a maximum time of 30 minutes; thirdly, we find elements with high technology that makes them vulnerable to children or the elderly; We also find devices with a poor operating machinery in quality of materials that with time and use of the machine can be damaged and cause the useful life of the device to decrease by 30%.